Computational aeroelastic analysis of a hovering W3 Sokol blade with gurney flap. (February 2015) - Pastrikakis, V.A.; Steijl, R.; Barakos, G.N.; Małecki, J.
Abstract: This paper demonstrates the potential effect of a gurney flap on the performance of the W3-Sokol rotor blade in hover. A rigid blade was first considered and the calculations were conducted at several thrust settings. The gurney flap was extended from 46%R to 66%R and it was located at the trailing edge of the main rotor blade. Four different sizes of gurney flaps were studied, 2%, 1%, 0.5% and 0.3% of the chord. The biggest flap proved to be the most effective. A second study considered elastic blades with and without the gurney flap. The results were trimmed at the same thrust values as the rigid blade and indicate an increase of aerodynamic performance when the gurney flap is used, especially for high thrust cases.